A Review of Sudarshan Kriya Yoga for Improving Antioxidant Status and Reducing Anxiety in Adults - Dhanurkar, Santosh; Pandey, Vipin; Shelke, Vandna; Patel, Ritu; Singhai, Vivek (International Research Journal of Ayurveda & Yoga, 2023)
Breathing exercises are frequently advised to promote improved organ function, stress reduction, relaxation, and control over psychophysiological states. It has been demonstrated that yogic breathing, which is the control of breath movement, improves immunological function, autonomic nervous system imbalances, and illnesses linked to stress or psychology. This study aimed to evaluate and present a thorough analysis of the physiological mechanisms, the mind–body connection, and the advantages of Sudarshan Kriya Yoga (SKY) in various therapeutic settings. Medline, PsychINFO, EMBASE, and Google Scholar were among the many internet resources that were looked up. Articles on SKY were chosen after a thorough screening of all the results. We looked through these articles’ references to see if there were any more, perhaps pertinent articles. A variety of cyclical breathing rhythms, from slow and soothing to fast and invigorating, are used in SKY, a special kind of yogic breathing technique. An increasing body of research indicates that SKY may be an advantageous, low-risk, low-cost supplement to the treatment of stress, anxiety, depression, post-traumatic stress disorder, medical conditions linked to stress, substance misuse, and the rehabilitation of criminal offenders.